Shadowing during intraoperative optical coherence tomography-assisted vitreoretinal surgery: clinical significance and reduction strategy - Carlos Reyna, Kevin Erick Gabriel; Justus Liebig University Giessen (My University, 2024)
Purpose: To analyze the clinical significance of signal shadowing during intraoperative optical coherence tomography (iOCT)-assisted vitreoretinal surgery caused by intraocular instruments, intraocular dyes, and vitreous substitutes, and to objectively quantify its impact on iOCT imaging in order to produce strategies to mitigate its negative effects. Methods: This is a retrospective observational study of postoperative image analysis from one hundred seventeen (117) patients who underwent iOCT-assisted vitrectomy. The image data were assigned to three groups: intraocular instruments, intraocular dyes, and vitreous substitutes. The data was then processed using graphic software to measure the grade of picture quality distortion and compared to paired image controls without clinically perceptive interference; consequently, analyzed statistically. Newly designed vitreoretinal instrument prototypes aimed at reducing baseline interference were also similarly tested. Results: The intraocular portion of all studied vitreoretinal instruments caused a high average gray level interference compared to controls ranging from 32% to 68% reduction, obscuring the area of interest significantly. The tips of the instruments produced low-grade shadowing, allowing the underlying tissue to be distinguished. The analyzed dyes demonstrated a wide interference range: ICG (-75.12%), and triamcinolone (-26.13%) showed dose-dependent high shadowing, while VITREODYNE™ (49.3%) and brilliant blue (15.0%) exhibited no perceived distortions whilst increasing average gray levels. All analyzed vitreous substitutes (air, SF6, C3F8, PFCL, and silicone oil) showed an insignificant shadowing effect on iOCT. The novel instrument prototypes showed an average gray level reduction of only 9.01%. Conclusions: Certain dyes and vitreous substitutes produce a negligible shadowing effect compared to controls and other dyes, giving an advantage during real-time iOCT imaging. All analyzed intraocular instruments showed a significant interference that should prompt the development of new imaging techniques or the implementation of materials with low-grade interference to overcome a clinically relevant shadowing effect on iOCT, maximizing the technology’s visual accuracy and in vivo surgical diagnostic aid proficiency.
Keywords: iOCT; Vitreoretinal surgery; ddc:610